Impacto de la automatización en el desarrollo de ventajas competitivas en empresas de almacenamiento de Lima Metropolitana - Abad Borjas, Denisse Nicole (2023)
The COVID-19 pandemic brought many changes at all levels and many companies had to transition to a new reality where agility and resilience are important factors. However, there are many companies that have not yet adapted their operations to respond to these new market needs and are in danger of not surviving in this new competitive environment. Another of the consequences of the pandemic was the accelerated growth of electronic commerce that demands that companies, especially those that offer storage services, be innovative and efficient in their operations. That is why we present automation as an alternative to solve these new challenges that these companies are currently experiencing through a study of variables, as well as field work that has allowed us to validate our hypotheses.